The Influence of Motivation, Perception and Work Environment on the Performance of PDAM Tirta Pakuan Employees, Bogor City - Meidiana, Muhammad Aldi (International Journal of Advanced Multidisciplinary, 2023)
This research examines the relationship between motivation, perception and work environment on the performance of PDAM Tirta Pakuan Bogor City employees. In scientific literature study articles in the field of Human Resources (HR), there are variables tested, namely work motivation (X1), perception (X2), and environment (X3), employee performance (Y1). The aim of this research is to study the impact of motivation, perception and working conditions on the performance of PDAM Tirta Pakuan Bogor City employees. This research, which contains a Literature Review article, uses a quantitative descriptive approach in conducting field research. The aim of this research is to create an understanding of the factors that influence the work motivation, perceptions and work environment of PDAM Tirta Pakuan Bogor City employees in order to improve work performance. This article states that motivation has an impact on performance, perception can also influence performance, and the work environment also has an influence on employee performance.